2019
DOI: 10.3171/2019.4.peds18612
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal resection versus open surgery for pediatric craniopharyngioma: comparison of outcomes and complications

Abstract: OBJECTIVECraniopharyngioma represents up to 10% of pediatric brain tumors. Although these lesions are benign, attempts at gross-total resection (GTR) can lead to serious complications. More conservative approaches have emerged but require adjuvant radiation. Endoscopic endonasal surgery (EES) aimed at GTR has the potential to result in fewer complications, but there has been limited comparison to open surgery. The authors performed a review of these two approaches wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…A total of 25 studies met inclusion criteria for qualitative and quantitative analysis. 1,7,11,21-42 See Figure 1 for a summary of search results. A funnel plot indicating less likelihood of publication bias across studies is presented in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 25 studies met inclusion criteria for qualitative and quantitative analysis. 1,7,11,21-42 See Figure 1 for a summary of search results. A funnel plot indicating less likelihood of publication bias across studies is presented in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective review, Madsen et al 13 explored the outcomes and complications of an EES (n = 28) versus open surgery (n = 15) for craniopharyngiomas in pediatric patients with a mean age of 8.2 years. A matched cohort analysis was performed to compare the 11 patients with the largest tumors in the endoscopic group to 11 patients in the open surgery group.…”
Section: Resultsmentioning
confidence: 99%
“…When EES is utilized as the first-line treatment for pediatric craniopharyngiomas, patients experience better outcomes and reduced recurrence rates overall compared to those for whom EES is a secondary procedure, 9,19 although this is confounded by the fact that lesions requiring staged treatment or reoperation are inherently more likely to present with increased rates of complications and recurrence. Compared to microsurgery, EES was identified to be superior by Madsen et al 13 after controlling for tumor size. It should be noted that directly comparing transcranial approaches to EES is complicated by inherent selection bias such that EES is typically reserved for smaller sellar lesions, as purely suprasellar craniopharyngiomas are believed to be better treated with microsurgery.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment choice should be tailored individually given the high survival rate and potential lifetime complications related to injury to the optic apparatus or hypothalamus . Madsen et al demonstrated that GTR is possible in 85.7% of endonasal cases vs 53.3% in open approaches and the recurrence rate (40% vs 14.2%) and need for adjuvant therapy (20.0% vs 10.7%) are higher in open approaches . This trend toward improved resection and decreased recurrence with judicious application of endonasal approaches to pediatric craniopharyngioma are seen in multiple additional series .…”
Section: Discussionmentioning
confidence: 99%